2019
DOI: 10.1002/jcaf.22434
|View full text |Cite
|
Sign up to set email alerts
|

Internal audit standard compliance, potentially competing duties, and external auditors' reliance decision

Abstract: This article explores the impact of two previously overlooked characteristics, compliance with Institute of Internal Auditors (IIA) standards and the presence of potentially competing duties, on external auditors' perceptions of internal audit competence, objectivity, and, in turn, their willingness to rely on the internal audit function. This research finds that external auditors consider internal audit functions to be more competent and objective when they fully comply with IIA standards and that external au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…to the IAF directly or through the management). Prior research suggests that external auditors seem to have over-relied on IA performance as a reliable watchdog (Breger et al, 2020). Therefore, the psychological experience of powerlessness in the face of warning signs causes IA to remain silent.…”
Section: An Appropriate Organisational Position For Iamentioning
confidence: 99%
“…to the IAF directly or through the management). Prior research suggests that external auditors seem to have over-relied on IA performance as a reliable watchdog (Breger et al, 2020). Therefore, the psychological experience of powerlessness in the face of warning signs causes IA to remain silent.…”
Section: An Appropriate Organisational Position For Iamentioning
confidence: 99%
“…For example, Archambeault et al (2008) found that internal audit disclosures promote investors' understanding of the internal audit function in governance. Breger et al (2020) argued that external auditors have increased their reliance on internal auditing since the Sarbanes-Oxley Act 2002 and found that these auditors are willing to rely on internal audit work if they adhere to the standards on internal auditing practices issued by the Institute of Internal Auditors (IIA). Cular et al ( 2020) examined the reliance of external auditors on the internal audit function and found that if such function provides consulting services on enterprise risk management, then the reliance of external auditors will only increase when the audit committee effectiveness is strengthened.…”
Section: Internal Auditingmentioning
confidence: 99%
“…Cular et al ( 2020) examined the reliance of external auditors on the internal audit function and found that if such function provides consulting services on enterprise risk management, then the reliance of external auditors will only increase when the audit committee effectiveness is strengthened. Both Breger et al (2020) and Cular et al (2020) studies were examine in an environment where external auditors are no longer allowed to provide internal audit services to their audit clients. The regulation applies both in the US Sarbanes Oxley Act (2002) and Malaysia (2008).…”
Section: Internal Auditingmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, authors have identified several gaps and have encouraged continual research in the area of IA. Breger, Edmonds, and Ortegren (2020) thought that the perspective of EA towards IA was worthy of research since EA often relies on the work of the IA. However, Soh and Martinov‐Bennie (2011) believed that the perceptions of all others in the CG mosaic should be sought toward IA.…”
Section: Introductionmentioning
confidence: 99%